Kompetensi Auditor, Independensi, Skeptisme Profesional dan Kualitas Audit - Renaldi Renaldi; Rizal Mawardi (Akuntabilitas, 2021)
The emergence of several cases that befell well-known Public Accounting Firms in Indonesia makes researchers want to test so that the purpose of this study is to determine the effect of auditor competence, auditor independence, and professional skepticism on audit quality. This study uses a survey method with a questionnaire. The sample in this study is an auditor who works at a Public Accounting Firm in South Jakarta. The sampling technique used was random sampling method. The sample of this research was conducted in 10 Public Accounting Firms with 77 auditors as respondents. The results of this study indicate that auditor competence, auditor independence, and professional skepticism have a positive effect on audit quality. This result implies that it is important for an auditor to have adequate competence, independent attitude and professional skepticism while carrying out audit engagements.How to Cite:Renaldi., & Mawardi, R. (2021). Kompetensi Auditor, Independensi, Skeptisme Profesional dan Kualitas Audit. Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 153-168.